Improvement of tinnitus, anxiety, and depression following cochlear implant surgery: a prospective cohort study - Pauliana Lamounier; Pauliana Lamounier; Victória Franco Gonçalves; Isabela Carvalho Queiroz; Débora Aparecida Gobbo; Marina Nahas Dafico Bernardes; Claudiney Cândido Costa; Hugo Valter Lisboa Ramos; Fayez Bahmad (Frontiers in Audiology and Otology, 2024)
IntroductionHearing loss affects ~1. 5 billion people worldwide and is the greatest risk factor for tinnitus, a condition that can further worsen people's quality of life, lead to high anxiety and depression, and affect general health and wellbeing.ObjectivesThis study aimed to assess the impact of cochlear implants (CIs) on tinnitus perception and quality of life and their relationship with psychological disorders, such as depression and anxiety.MethodsThirty adults with profound bilateral hearing loss who were candidates for CI surgery and experienced tinnitus were assessed using the Tinnitus Handicap Inventory (THI), the Visual Analog Scale (VAS), the World Health Organization Quality of Life Instruments–Bref (WHOQOL-BREF), and the Hospital Anxiety and Depression Scale questionnaires at four different time points: preoperatively, 7 days after cochlear implant activation, and 3 and 6 months after cochlear implant surgery. The International Outcome Inventory CI was applied at 3 and 6 months, and the Glasgow Benefit Inventory (GBI) questionnaire was applied at 6 months.ResultsThe VAS and THI scores improved; however, significant improvements were only observed in the THI scores 6 months post-surgery. Time spent using hearing aids did not correlate significantly with speech recognition test scores, nor were the changes in the preoperative THI score and VAS scores or the changes in the speech recognition test scores 6 months post-surgery significantly correlated. We observed a decrease in anxiety and depression scores at the 6-month follow-up compared to the preoperative period.ConclusionThe THI scores significantly increased after CI surgery, suggesting that the tinnitus had improved. Improved anxiety and depression scores after CI surgery were also observed. The WHOQOL-BREF quality-of-life self-evaluation scores, as well as the environment and general domains, significantly improved as well.